PTU-013 Simulation-based Human Factors Training In Endoscopy – Putting The Team In The Spotlight. (9th June 2014) - Webster, S; Howson, W; McKay, A; Smith, G
Abstract : Introduction: Human factors play an important role in adverse incidents and complaints in healthcare. Simulation is increasingly recognised as a safe and effective platform for human factors training. We propose that multiprofessional team-based simulation courses could enhance staff training, staff engagement, patient safety and patient experience in the endoscopy unit. Methods: We designed and delivered four in-situ multiprofessional simulation courses for established endoscopy teams across North West London, using recent clinical incident and complaints data to inform scenario selection and debriefs. We developed learning resources including a faculty information sheet, pre and post course questionnaires, scenario descriptions and an introductory presentation. We procured an OGD and colonoscopy simulator and invited a patient actor to contribute to scenarios and debriefs. Video feedback was used to inform peer-led discussions. We collected quantitative and qualitative pre and post course data including participant demographics, and Likert scores for course enjoyment, usefulness, relevance and realism. Data was analysed descriptively. Results: A total of 47 endoscopy staff participated in the courses (course size 8–15), including 32 nurse assistants, 11 endoscopists, 3 health care assistants and 1 porter. 70% were female, 55% were aged 35 to 50 and 60% had less than 5 years experience in endoscopy. Post course data analysis showed high Likert scores across all measured domains (1 poor – 5 excellent): 4.74 (enjoyment), 4.81 (usefulness), 4.80 (relevance), 4.33 (realistic). 85% felt that their confidence in managing similar situations in real life had improved. Qualitative data was universally positive, and included: "quality feedback", "makes you reflect on better practice", "shared learning", and "there is a real need for courses such as this". Conclusion: Endoscopy teams value simulation based multiprofessional learning platforms for human factors training. We believe that 3 key features enhanced learning and course effectiveness: in-situ delivery of courses with established teams, empowering team members of all professional backgrounds to voice clinical concerns, and active participation with supported feedback. We believe that multiprofessional learning platforms have an important place in healthcare improvement and endoscopy teams are well placed to benefit. References: Sedlack RE, Kolars JC. Computer simulator training enhances the competency of gastroenterology fellows at colonoscopy: results of a pilot study. Am J Gastroenterol . 99:33–37 Yee B et al . Nontechnical skills in anesthesia crisis management with repeated exposure to simulation-based education. Anesthesiology 103:241–8 Disclosure of Interest: None Declared.